Synthesis of 3,4-Disubsituted Isoxazoles via Enamine [3+2] Cycloaddition - Jia, Qian-fa; Benjamin, Pooi Ming Shurn; Huang, Jiayao; Du, Zhiyun; Zheng, Xi; Zhang, Kun; Conney, Allan H.; Wang, Jian (Synlett, 2013)
Enamine-triggered [3+2]-cycloaddition reactions of aldehydes and N-hydroximidoyl chlorides in the presence of triethylamine give rise to 3,4-disubstituted isoxazoles upon oxidation of the cycloadduct 3,4,5-trisubstituted 5-(pyrrolidinyl)-4,5-dihydroisoxazoles. This offers a high yielding, regiospecific and metal-free synthetic route for the synthesis of 3,4-disubstituted isoxazoles.
Keywords: isoxazole; enamines; 1,3-dipoles; [3+2] cycloaddition